742 INITIAL RESULTS OF THE 'TUBELESS' OESOPHAGUECTOMY: LESS IS MORE. (17th September 2021) - Abelló, David; Navío, Ana; Bruna, Marcos; Rodríguez, Pedro; Pérez, Carla; Mingol, Fernando; Vaqué, Javier; García-Granero, Eduardo
Abstract: : Oesophageal cancer surgery is a complex procedure with high morbidity and mortality rate. High volume centres, complete multidisciplinary support and clear clinical guidelines are required to obtain adequate results. One of the objectives of multimodal rehabilitation programs in this field is to reduce surgical aggression. Initial experience with the tubeless oesophagectomy technique is described. Methods: Description of the technique and perioperative management of tubeless oesophagectomy. We performed a 3-stage esophagectomy with a minimally invasive approach, without NGT placement or any type of drainage. The procedure includes the so-called phantom jejunostomy, which require of fixing the first jejunal loop to the parietal peritoneum in order to position a percutaneous catheter if necessary. All patients were extubated at the end of the surgery, remaining in the ICU with high-flow glasses for the first 24–48 hours. Also in the first 2 days, the urinary catheter and the epidural catheter were removed, sitting and fluid tolerance began. Results: Beteween June–November 2020 6 patients were operated on. Median age was 60 years (range: 52–70), 83.3% were squamous cell carcinoma located in the middle oesophagus, 4 patients received neoadjuvant CROSS treatment. No intraoperative complications reported and a median stay of 7 days (range: 6–28). There was no anastomotic leak, nor need to place a jejunostomy, nor need to place a nasogastric tube and neither reoperation. A thoracic tube was necessary for chylothorax and another for pneumothorax (in a patient with acute respiratory distress). There was no mortality at 30 and 90 days after the procedure. Conclusion: Tubeless oesophagectomy is a feasible concept that can improve postoperative recovery in selected cases, reducing pain associated with drains and tubes, facilitating early mobilization and correct performance of respiratory physiotherapy exercises. Improving functional recovery and quality of life during the postoperative period. Studies with a greater number of cases and well designed are necessary to strongly evaluate this type of procedure.